Anthraquinones from the fungus Dermocybe sanguinea as textile dyes - Räisänen, Riikka (Research report / University of Helsinki, department of home economics and craft science = Helsingin yliopiston kotitalous- ja käsityötieteiden laitoksen julkaisuja, ISSN 1456-4912, 2002)
Abstract.
Keywords: kasvivärjäys; väriainekasvit